As metodologias ativas de aprendizagem como potencializadoras do sistema atencional - Bombana, Cheila Graciela Gobbo (2020)
The learning process in formal education goes through a challenging moment in view of the transformations brought about by Digital Technologies, in this social context the lack of attention from students has become a problem in schools, implying new ways of teaching how to learn. In view of this situation, interest in Active Learning Methodologies emerges, didactic strategies based on different theoretical currents that, it is believed, can collaborate for a greater engagement of students in the classroom. In this sense, the following question will guide our research: what are the influences of educational processes based on Active Learning Methodologies on the Attentional System of high integrated school students from IFRS - Campus Sertão? Therefore, the main objective of this study is to analyze manifestations of the functions of the Attention System in high school students integrated in IFRS - Campus Sertão in the face of educational processes based on Active Learning Methodologies. An exploratory qualitative study with bibliographic research was developed, having Pozo (2008) and Sternberg (2008) as main references for understanding the Attention System, and Bacich and Moran (2018) to deepen the knowledge on Active Learning Methodologies. Empirical research is classified as Pedagogical Intervention Research and was carried out through data triangulation, using the instruments: participatory observation, questionnaire and focus group. The results show considerable activation of the students' Attention System functions through the use of Active Learning Methodologies Flipped Classroom and Design Thinking. Greater influence was perceived on the function of the Attention System Selection, followed by the Control and Surveillance functions. It was noticed that the Design Thinking approach, supported by Digital Technologies, was of great importance to attract and keep students' attention, contributing to involve them in the learning process. Thus, we show that the Active Learning Methodologies Flipped Classroom and Design Thinking are presented as didactic strategies to enhance the manifestation of the functions of the Attention System. It is hoped that these results will stimulate further research on Active Methodologies as didactic strategies that stimulate attention and favor critical and reflective learning, showing them as a powerful alternative in this increasingly challenging educational scenario.